2015
DOI: 10.1039/c5fo00287g
|View full text |Cite
|
Sign up to set email alerts
|

Targeted plasma metabolome response to variations in dietary glycemic load in a randomized, controlled, crossover feeding trial in healthy adults

Abstract: Low versus high glycemic load (GL) diet patterns are inversely associated with obesity and chronic diseases such as cancer and cardiovascular disease. These associations persist beyond the protection afforded by increased fiber alone, representing an important gap in our understanding of the metabolic effects of GL. We conducted a randomized, controlled, crossover feeding trial of two 28-day diet periods of high and low GL. Using LC-MS, targeted metabolomics analysis of 155 metabolites was performed on plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…Mass spectrometry (MS) or nuclear magnetic resonance (NMR) metabolomics analyses of biological fluids can precisely quantify metabolic states in individuals to better characterize disease and to better understand response to treatment. In our work referenced above, 63 targeted metabolomics demonstrated that circulating concentrations of amino acids and urea cycle intermediaries were reduced after traumatic injury and gradually returned toward levels seen in healthy, uninjured individuals over the first week after injury. In a second cohort of trauma victims, we observed changes in circulating concentrations of amino acids and urea cycle intermediaries within days, specifically in response to starting EN 65 .…”
Section: Current Practicementioning
confidence: 81%
See 1 more Smart Citation
“…Mass spectrometry (MS) or nuclear magnetic resonance (NMR) metabolomics analyses of biological fluids can precisely quantify metabolic states in individuals to better characterize disease and to better understand response to treatment. In our work referenced above, 63 targeted metabolomics demonstrated that circulating concentrations of amino acids and urea cycle intermediaries were reduced after traumatic injury and gradually returned toward levels seen in healthy, uninjured individuals over the first week after injury. In a second cohort of trauma victims, we observed changes in circulating concentrations of amino acids and urea cycle intermediaries within days, specifically in response to starting EN 65 .…”
Section: Current Practicementioning
confidence: 81%
“…Genomics, proteomics, and metabolomics provide the tools for systemwide interrogation of biological systems and ultimately will guide personalized medicine. Metabolomics is the high‐throughput study of small molecules like amino acids, nitrates, sugars, and lipids and may be ideally suited to guiding protein supplementation 63 . Using targeted metabolomics, we have observed changes in pathways related to protein, carbohydrate, and nucleic acid synthetic pathways and in pathways related to oxidative stress in the first week after traumatic injury 64 .…”
Section: Current Practicementioning
confidence: 99%
“…Numerous studies have used metabolomics to characterize dietary intakes, although these have $1 limitations, such as crosssectional observational design subject to confounding by nondietary factors, lack of control groups, small sample size, use of a limited panel of metabolites, low resolution of profiling techniques, and data analysis based exclusively on clustering methods rather than single metabolites (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The aim of the present study was to conduct high-throughput metabolomics analysis of plasma samples from a carefully controlled crossover feeding study, unconfounded by weight loss, to determine whether a molecular "fingerprint" could distinguish individuals consuming 3 diets differing in macronutrient composition.…”
Section: Introductionmentioning
confidence: 99%
“…Barton et al. found significant differences in 14 plasma metabolites out of a total of 155 analyzed in 19 healthy adults after a crossover trial of two 28‐day diet periods of high‐ and low‐GI diets . Similarly, the second study was conducted with 21 obese adults following a crossover design trial for 4 weeks in each period.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic modulation after dietary interventions with differential GI content was first identified in 24 h urine samples from overweight subjects . However, a few studies have used metabolomics to identify changes in circulating metabolites after subjects follow a LGI diet for a short length of time . These studies found a significant modulation of plasma metabolites, including amino acids and specific lipid species, in the LGI diet intervention.…”
Section: Introductionmentioning
confidence: 99%